Synthesis, bioactivity evaluation and computational studies of bisindolylmethane and flavone derivatives / Syahrul Imran Abu Bakar - Abu Bakar, Syahrul Imran (Institute of Graduate Studies, UiTM, 2016)
Bisindolylmethane and flavone are well-known natural product scaffolds having important pharmacophores and they have gained tremendous interest owing to their remarkable potency and activity profile towards various target diseases. In this study novel bisindolylmethanes and flavones were synthesized to identify potential inhibitors for bacterial infection, cancer, and diabetes. One hundred twenty-nine (129) bisindolylmethane derivatives (Schiff base, thiourea, sulfonamide, and hydrazone) and 43 flavone derivatives (hydrazone and ether) were synthesized, evaluated for various in vitro bioactivities, and analyzed through computational studies to identify possible inhibition mechanisms. Antibacterial activity of bisindolylmethane Schiff bases showed that most compounds moderately inhibit Salmonella typhi, S. paratyphi A and S. paratyphi B bacterial strains. The results also reveals that compounds having halides and nitro substituents showed best antibacterial activity. Bisindolylmethane thioureas and sulfonamides were tested for carbonic anhydrase II inhibition activity. Molecular docking results suggest that nitro substituent at para position interacts well with Zn2+ ion and interferes with the Zn-OH-Thr199-Glu106 hydrogen bond network. Bisindole hydrazone in this study were synthesized through a three-step reaction. β-Glucuronidase inhibitory property of some derivatives were found to be very potent (0.1-83.5 μM). Docking studies showed that active compounds should have two or more hydroxyl groups substituted on carbon adjacent to each other for good interactions to take place…